Myopathy secondary to empagliflozin therapy in type 2 diabetes - Frank Gao; Stephen Hall; Leon A Bach (Endocrinology, Diabetes & Metabolism Case Reports, 2020)
Sodium/glucose co-transporter 2 (SGLT2) inhibitors are novel oral hypoglycaemic agents that are increasingly used in the management of type 2 diabetes mellitus (T2DM). They are now recommended as second-line pharmacotherapy (in conjunction with metformin) in patients with type 2 diabetes and established atherosclerotic heart disease, heart failure or chronic kidney disease due to their favourable effects on cardiovascular and renal outcomes. We report a case of a 69-year-old man who developed muscle pain, weakness and wasting after commencing the SGLT2 inhibitor empagliflozin. This persisted for 1 year before he underwent resistance testing, which confirmed muscle weakness. His symptoms resolved within weeks of ceasing empagliflozin, with improvement in muscle strength on clinical assessment and resistance testing and reversal of MRI changes. No other cause of myopathy was identified clinically, on biochemical assessment or imaging, suggesting that empagliflozin was the cause of his myopathy.